STUDY ON THE IMPACT OF WORKING FACILITIES AS A MODERATING FACTOR FOR COMPENSATION AND BENEFIT UTILIZING THE THEORY OF PLANNED BEHAVIOR TOWARD ACCOUNT OFFICERS’ INTENTION TO STAY IN INDONESIAN SHARIA BANKING UNDER THE GRAMEEN MODEL - Dian Heryanti Handayani; Rida Amanda; Anggun Laela Wulandari; Ario Setra Setiadi (RADJA PUBLIKA, 2026)
This study investigates the determinant factors affecting the intention to stay among Account Officers at Indonesia's sole sharia bank employing the Grameen model to serve underprivileged women. Grounded in the Theory of Planned Behavior (TPB), it analyzes the influence of attitude, subjective norms, and perceived behavioral control on retention intentions while evaluating the moderating role of compensation and benefits, particularly working facilities. Data were gathered via a structured survey and analyzed using Partial Least Squares–Structural Equation Modeling (PLS-SEM) to evaluate the measurement model and structural relationships. Results indicate that all three TPB constructs significantly predict intention to stay, with perceived behavioral control emerging as the strongest factor. This underscores that Account Officers' confidence in managing job demands is pivotal to their retention decisions. However, compensation and benefits did not moderate these relationships, implying that in mission-driven roles like microfinance, financial incentives do not substantially influence the psychological and social drivers of sustained employment. These findings extend TPB's application to sharia microfinance banking, providing empirical insights into retention in community-oriented jobs. They highlight the importance of bolstering psychological support, supervision, and social ties as more effective retention strategies than compensation alone.